Impact of Various Carbon Sources on the Growth Efficiency, Antioxidant Efficacy, and Immunity of Clariid Catfish Clarias gariepinus (Burchell 1822) - Blessing Aderonke Oguntokun; Ayomide Miracle Oyelade; Tunde Olowolafe; Omoniyi Popoola (Aquatic Sciences and Engineering)
The study examined the effects of various carbon sources on Clarias gariepinus (6.18±0.2g and 8±0.13 cm) growth efficiency, antioxidant efficacy, and immune function. The bioflocs system was developed using four carbon sources: tapioca, cassava flour, rice bran, and molasses. The fish were raised in concrete tanks for 10 weeks, and their water quality was monitored, after which they were challenged. The results demonstrated that the treatments significantly differed in terms of both survival rate and water quality parameters. Fish reared in biofloc systems exhibited significantly higher total cholesterol, total protein, superoxide dismutase (SOD), Lyzosome (LYZ), and Myeloperoxidase (MPO) activities compared with the control group. However, there was a reduction in the activities of ALT, AST, total glucose, and antiprotease in biofloc-treated C. gariepinus compared with the control. Expression of the IL-1 gene in the intestines was significantly elevated in fish raised in biofloc. Similarly, the transcription of GPX, GSR, IL-1, and IL-8 genes in the gut and liver of biofloc-treated fish was considerably enhanced. Applying biofloc to the rearing medium can enhance fish growth efficiency, immune system response, and the transcription of genes associated with immunity and antioxidant activities in C. gariepinus. The degree of immune system stimulation by the BFT system is impacted by the carbon source.